2005
DOI: 10.1016/j.jimonfin.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale systematic risk

Abstract: In this paper we propose a new approach to estimating systematic risk (the beta of an asset). The proposed method is based on a wavelet multiscaling approach that decomposes a given time series on a scale-by-scale basis. The empirical results from different economies show that the relationship between the return of a portfolio and its beta becomes stronger as the wavelet scale increases. Therefore, the predictions of the CAPM model should be investigated considering the multiscale nature of risk and return. © … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
136
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(145 citation statements)
references
References 30 publications
9
136
0
Order By: Relevance
“…The systematic risk in a Capital Asset Pricing Model was estimated over different granularities, [27], where it was shown that the return of a portfolio and its beta b becomes stronger as the scale increases for the S&P 500. This technique was then applied to the markets of various other countries, [28], with similar results also found. The dependence of stock return cross-correlations on the sampling time scale is known as the Epps effect [29].…”
Section: Introductionmentioning
confidence: 59%
“…The systematic risk in a Capital Asset Pricing Model was estimated over different granularities, [27], where it was shown that the return of a portfolio and its beta b becomes stronger as the scale increases for the S&P 500. This technique was then applied to the markets of various other countries, [28], with similar results also found. The dependence of stock return cross-correlations on the sampling time scale is known as the Epps effect [29].…”
Section: Introductionmentioning
confidence: 59%
“…They show that both regression components have scale-specific predictability on low frequency. Other studies using the frequency domain in asset pricing models include Otrok et al (2002), Gençay et al (2005) and Yu (2012).…”
Section: Recent Surge Of Frequency-based Methods In Financial Economicsmentioning
confidence: 99%
“…Wavelets in finance are primarily used as a signal decomposition tool (e.g. [32], [16], [14], [17], [18], [51]), or a tool to detect and return comovement between CEE and developed European stock markets. To our knowledge, this is the first study to apply this methodology to CEE stock markets.…”
Section: Introductionmentioning
confidence: 99%